Body recomposition: Can trained individuals build muscle and lose fat at the same time? - Barakat, C.; Pearson, J.; Escalante, G.; Campbell, B.; De Souza, E. O. (Strength and Conditioning Journal, 2020)
Despite the lack of standardized terminology, building muscle and losing fat concomitantly has been referred to as body recomposition by practitioners. Although many suggest that this only occurs in untrained/novice and overweight/obese populations, there is a substantial amount of literature demonstrating this body recomposition phenomenon in resistance-trained individuals. Moreover, 2 key factors influencing these adaptations are progressive resistance training coupled with evidence-based nutritional strategies. This review examines some of the current literature demonstrating body recomposition in various trained populations, the aforementioned key factors, nontraining/nutrition variables (i.e., sleep, hormones), and potential limitations due to body composition assessments. In addition, this review points out the areas where more research is warranted.